متعارض احادیث میں ترجیح کے ذریعے اختلاف کو دور کرنے میں امام طحاوی رحمہ اللہ کا منہج: Imām Al-Tahawʿī’s Approach about Giving Preference to Resolve Contradiction in Ḥadīth - Dr. Muhammad Waris Ali (jihat-ul-islam, 2021)
Some of the Ḥadīths seem to be against one another and create confusion. Early Muslim theologian, al-Ṭaḥāwī (d321/933) has discussed this issue in his book Sharaḥ M’āni al-Athār and derived rules in the light of Qur’an and Sunnah to resolve contradiction. This article aims to highlight the principles of preference used by al-Ṭaḥāwī (d321/933) in his book to resolve contradiction in Ḥadīths. The examples from his book have been taken, discussed and analyzed. Al-Ṭaḥāwī (d321/933)seems to give preference to the Ḥadīthsthat are authentic and have more chains of narrating the Ḥadīths. He also prefers the Ḥadīth which is clearer in its meaning to the complicated one. It is also notable that he rejects the Ḥadīth that has weak narrators in comparison with sound narrators.